From Story to Sale: The Mediating Role of Comsumer Enggagement in Short Video Marketing at Petro’s Coffee - S, Sebrina; Erwansyah, Erwansyah; Widodo, Slamet (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The rapid advancement of digitalization has transformed marketing strategies in Indonesia’s food and beverage (F&B) industry, with short video marketing emerging as a key approach to reaching modern consumers. This study aims to examine the effect of short video marketing on consumers’ purchase intention, with consumer engagement serving as a mediating variable among Petro’s Coffee customers. A quantitative approach was employed using a cross-sectional survey design involving 150 respondents aged 18–45 years who had been exposed to Petro’s Coffee short video content within the past three months. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The theoretical foundation of this study integrates the Stimulus–Organism–Response (S-O-R) framework to explain the psychological mechanisms underlying consumer responses. The results indicate that short video marketing has a positive and significant effect on consumer engagement, consumer engagement positively and significantly influences purchase intention, and consumer engagement significantly mediates the relationship between short video marketing and purchase intention. These findings highlight consumer engagement as a key mechanism in translating short video marketing stimuli into consumers’ behavioral responses. Practically, this study provides strategic implications for F&B industry practitioners in optimizing short video marketing by strengthening consumer engagement to enhance purchase intention